2016
DOI: 10.4067/s0718-381x2016000200013
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Wet Bonding Technique: 18-month Clinical Evaluation

Abstract: ABSTRACT:The objective of this randomized clinical trial was to evaluate the clinical performance up to 18 months of restorations placed using ethanol-wet bonding technique (EWBT) compared with the three-step etch-and-rinse (TSER) and one-step self-etching (OSSE) approaches. Ninety-three non-carious cervical lesions (31 for each group) were restored by one experienced operator in 17 patients under relatively dry conditions using gingival retraction cord, cotton rolls and saliva ejector. Each adhesive system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…17,35 However, clinical trials evaluating the EWBT did not show significant differences after 12 or 18 months, with retention rates for the EWBT at 91.67% and 93.55%. 16,36 Technique differences in those studies are related to the use of a formulated hydrophobic primer (hydrophobic bond diluted in ethanol in a concentration of 10% or 50 w% ethanol) or the ethanol not being actively applied. 12,15,16,36,37 Although no differences were detected when compared with the control groups, one study reported that the 91.7% success for the EWBT in comparison with the 100% success rate for the control could be related to the sensitivity of the EWBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,35 However, clinical trials evaluating the EWBT did not show significant differences after 12 or 18 months, with retention rates for the EWBT at 91.67% and 93.55%. 16,36 Technique differences in those studies are related to the use of a formulated hydrophobic primer (hydrophobic bond diluted in ethanol in a concentration of 10% or 50 w% ethanol) or the ethanol not being actively applied. 12,15,16,36,37 Although no differences were detected when compared with the control groups, one study reported that the 91.7% success for the EWBT in comparison with the 100% success rate for the control could be related to the sensitivity of the EWBT.…”
Section: Discussionmentioning
confidence: 99%
“…14 Few clinical studies have evaluated the EWBT as a dentin pretreatment. 15,16 The use of ethanol has been evaluated with a modified progressive technique 16 and by using two coats of hydrophobic bonding resin, 15 with no significant differences because of the technique in these two clinical studies. In another study, a formulated experimental hydrophobic adhesive containing ethanol in its hydrophobic primer composition resulted in acceptable performance.…”
Section: Introductionmentioning
confidence: 99%